The Relationship between Spiritual Well-being and Organizational Virtuousness with Performance of Secondary School Teachers in Bandar Lengeh City, 2017 - Hamed Delam; Fatemeh Ghasemi; Esmaeil Kavi; Behnam Masmouei; Mozhgan Jokar; Mohammad rafi Bazrafshan (Shiraz University of Medical Sciences, 2019)
Background: Job performance is one of the most important variables in industrial and organizational psychology and its importance is clear to both individuals and organizations. The purpose of this study was to investigate the relationship between spiritual wellbeing and organizational virtuousness with the performance of high school teachers in Bandar Lengeh, Hormozgan Province. Methods: This was a cross sectional study conducted on all secondary teachers in Bandar Lengeh city, Hormozgan Province. 127 individuals were determined by using Morgan table. Measurement tools were 40-item Spiritual Well-being Questionnaire, 15-item of Organizational Virtuousness Questionnaire, and the 12-item Job Performance Questionnaire. Level of statistical significance was set at P<0.05. Results: The majority of respondents (77%) were men. 71% (n=90) of the respondents had a bachelor's degree. The findings of this study showed that there was a positive and significant relationship between spiritual well-being and its dimensions (relationship with God, self-relationship, relationship with others, and relationship with nature) with the performance of high school teachers (P<0.001). Also, there was a positive and significant relationship between organizational virtuousness and its dimensions (optimism, trust, sympathy, cohesion, and forgiveness) with the performance of high school teachers (P<0.05). Conclusion: Based on the findings of this study, it can be said that enhancing spiritual well-being and organizational virtuousness can enhance the performance of secondary school teachers.